Estimation of Mangrove Carbon Stock Using Normalized Difference Vegetation Index (NDVI) in Probolinggo, East Java - Dea Vega Emelia (Geographica: Science and Education Journal, 2021)
Probolinggo has the characteristics of the north coast of Java with large mangrove potential.  The total area of mangrove forest in Probolinggo is 476.6 ha with a research area of 75 ha covering Pilang, Ketapang, and Pesisir villages. This study aims to estimate the amount of mangrove carbon stock using Normalized Difference Vegetation Index (NDVI) from sentinel-2 data as a vegetation index. A Sampling of data was carried out using a stratified random sampling method and the data collected included trunk diameter, tree height, and mangrove identification using Mongmang software. There were six mangrove species, Rhizophora apiculate, Rhizophora mucronata, Rhizophora stylosa, Avicennia marina, Avicennia alba, and Soneratia alba. The results of the estimated carbon stock are divided into 4 classes from low to high which are marked in green to red. The value of carbon stock ranged from 95.96 tons/ha to 7089.50 tons/ha.  The results obtained by Pilang Village have high biomass and carbon stock values marked in red on the map. The results of the accuracy-test using standard error estimation (SE) get a small accuracy result of 10%.